Genetic improvement and related activities. Regional activities. Andean zone - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
In 1985 3 new cv. (Frijolica 0-3.1, Frijolica 0-3.2, and Frijolica LS-3.3) were released as a result of collaborative research between the Instituto Colombiano Agropecuario (ICA) and CIAT. At the Centro Regional de Investigacion (CRI)-La Selva (Antioquia, Colombia), 190 new advanced climbing bean lines were coded. A set of 32 lines has been selected on the basis of yield, disease resistance, and grain type, and these are currently in an advanced yield trial under low and high fertility. The best bush bean lines were PVA 476, PVA 7, and PVA 698. At CRI-Obonuco, 10 advanced climbing bean lines were planted in regional trials intercropped with maize in Ipiales, Contadero, and Cordoba. The most promising lines for possible var. release are AND 53 and ZAV 7. Bush bean lines were planted in El Tambo and Funes; at the 1st site the best new lines were AND 359, ICA 15551, and AND 311 and at the 2nd, the best new lines were PVA 3043, AFR 198, and PAV 3038. In 1985 a regional bush bean trial consisting of 7 bean lines, plus a local check, was organized in collaboration with ICA in the coffee growing region (medium alt. areas). Two small red mottle bean lines, PAI 29 and PAI 92, were superior to the other lines in overall yield. Web blight attacked the yield trial in many areas of Colombia; only PAI 29 and PAI 92 showed resistance. Because of the importance of this disease, a special observation nursery of 219 lines was formed in 1986. (CIAT)